Large‐Eddy Simulation of Oil‐Water Annular Flow in Eccentric Vertical Pipes. Issue 1 (25th November 2020) - Silva, Andhros G.; de Moraes, Deovaldo; Al Arni, Saleh; Solisio, Carlo; Converti, Attilio; Oliveira, Ricardo P. S.; Vianna, Ardson S.
Abstract: One of the difficulties related to oil exploration is transporting heavy oil since its high viscosity causes high‐pressure drop and energy consumption. In order to save energy, the core annular flow (CAF) can be applied where a two‐phase annular flow occurs, with peripheral water flowing offering a reduction in energy expenditure. The multiphase flow was studied experimentally in a simple purpose‐built unit. To theoretically handle the CAF, computational fluid dynamics simulations were done with the commercial package Ansys Fluent. The flow was considered turbulent, isothermal, incompressible, and 3D, and both stationary and transient cases were evaluated. The volume‐of‐fluid model was adopted for the multiphase system, and water/oil interface and turbulence phenomena were well predicted. Abstract : Oil‐water multiphase annular flow in eccentric vertical pipes was investigated both theoretically and experimentally. Computational fluid dynamics simulations were developed considering the 3D flow, stationary, and transient. The large‐eddy simulation proved to be a precise method to represent the interface. The swirl phenomena, observed experimentally, were also simulated satisfactorily.